Animal welfare and product quality in poultry breeding: Review - Bódi, László; Ferencz, Tímea Róza; Kisné Do thi, Dong Xuan; Thieu Ngoc, Lan Phuong; Szűcs, Endre; Kovácsné Gaál, Katalin; Szalay, István (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
The introduction of European Union’s rules regarding animal welfare in 1998 (XXVIII Act on protection and sparing of animals) significantly affected Hungarian breeders in many branches. Most radical transformation that arose from animal welfare regulations was the one for poultry generally and laying hens kept in cages particularly, but all farm animal production branches were affected to a certain extent. Animal welfare view and its becoming a branch of science has been developing since the 18th century. This process is shown in the first chapter of the paper. In the next chapters, after discussing the legal framework of animal welfare, major aspects of this topic is reviewed, including the effect of the environment and keeping conditions on animal welfare, relationship of it with behaviour and stress of animals, as well as practical aspects of animal welfare (breeding, keeping, transportation and slaughtering). In the last two chapters, research aspects of the methodology of animal welfare studies (on farm, physiology and ethology), and then the relationship of welfare with product quality in which poultry products (meat and egg) are quoted as examples, were discussed.The key aim of this review paper was to draw attention of professionals and lecturers to the importance of establishing scientific and educational bases of animal welfare development, in which authors made no secret of their opinion about the fact that animal welfare should not be handled as a simple legal issue, but it is also the standard of animal producers and consumers, being particular about both animal care and product quality.
Keywords: animal welfare; ethics; poultry breeding; product quality